Disentangling the Impacts of Anthropogenic Aerosols on Terrestrial Carbon Cycle During 1850–2014 - Yuan Zhang; Philippe Ciais; Olivier Boucher; Fabienne Maignan; Ana Bastos; Daniel Goll; Thibaut Lurton; Nicolas Viovy; Nicolas Bellouin; Laurent Li (Earth's Future, 2021)
Abstract Aerosols have a dimming and cooling effect and change hydrological regimes, thus affecting carbon fluxes, which are sensitive to climate. Aerosols also scatter sunlight, which increases the fraction of diffuse radiation, increasing photosynthesis. There remains no clear conclusion whether the impact of aerosols on land carbon fluxes is larger through diffuse radiation change than through changes in other climate variables. In this study, we quantified the overall physical impacts of anthropogenic aerosols on land C fluxes and explored the contribution from each factor using a set of factorial simulations driven by climate and aerosol data from the IPSL‐CM6A‐LR experiments during 1850–2014. A newly developed land surface model which distinguishes diffuse and direct radiation in canopy radiation transmission, ORCHIDEE_DF, was used. Specifically, a subgrid scheme was developed to distinguish the cloudy and clear sky conditions. We found that anthropogenic aerosol emissions since 1850 cumulatively enhanced the land C sink by 22.6 PgC. Seventy‐eight percent of this C sink enhancement is contributed by aerosol‐induced increase in the diffuse radiation fraction, much larger than the effect of the aerosol‐induced dimming. The cooling of anthropogenic aerosols has different impacts in different latitudes but overall increases the global land C sink. The dominant role of diffuse radiation changes found in this study implies that future aerosol emissions may have a much stronger impacts on the C cycle through changing radiation quality than through changing climate alone. Earth system models need to consider the diffuse radiation fertilization effect to better evaluate the impacts of climate change mitigation scenarios.